Soil-isolated fungus, Trichoderma viride, as biological control against Mango Anthracnose disease caused by Colletotrichum gloeosporioides. - Gonzales, Ralph Anthony (Iloilo City UPHSI, 2011)
The study aimed to find out the effectiveness of Trichoderma viride against mango anthracnose disease. The procedure included preparation of potato dextrose agar, isolation of Colletotrichum gloesosporioides, subculturing of Trichoderma viride, quality control test through spore germination, in vitro antagonistic test, data gathering for 7 consecutive days and data analysis using one-way ANOVA at a = 0.05 and Duncan's Multiple Range Test. The concentration 9X10^9 conidia/ml showed 96.82% inhibition, 2x10^7 conidia/ml showed 7.98% inhibition, 4x10^6 conidia/ml showed 17.97% inhibition, the positive control showed 18.28% inhibition, and the negative control showed 0% inhibition. Based on the results, the concentration 9x10^9 conidia/ml of Trichoderma viride is the most effective biological control against mango anthracnose disease caused by Colletotrichum gloeosporioides.
Research II : Research Manuscripts
Keywords: Trichderma viride